A Universal Route to Fabricate n‐i‐p Multi‐Junction Polymer Solar Cells via Solution Processing. Issue 5 (23rd March 2018) - Di Carlo Rasi, Dario; Hendriks, Koen H.; Heintges, Gaël H. L.; Simone, Giulio; Gelinck, Gerwin H.; Gevaerts, Veronique S.; Andriessen, Ronn; Pirotte, Geert; Maes, Wouter; Li, Weiwei; Wienk, Martijn M.; Janssen, René A. J.
Abstract : The interconnection layer (ICL) that connects adjacent subcells electrically and optically in solution‐processed multi‐junction polymer solar cells must meet functional requirements in terms of work functions, conductivity, and transparency, but also be compatible with the multiple layer stack in terms of processing and deposition conditions. Using a combination of poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate, diluted in near azeotropic water/ n ‐propanol dispersions as hole transport layer, and ZnO nanoparticles, dispersed in isoamyl alcohol as electron transport layer, a novel, versatile ICL has been developed for solution‐processed tandem and triple‐junction solar cells in an n‐i‐p architecture. The ICL has been incorporated in six different tandem cells and three different triple‐junction solar cells, employing a range of different polymer‐fullerene photoactive layers. The new ICL provided an essentially lossless contact in each case, without the need of adjusting the formulations or deposition conditions. The approach permitted realizing complex devices in good yields, providing a power conversion efficiency up to 10%. Abstract : Novel formulations of PEDOT:PSS in water/ n ‐propanol and ZnO nanoparticles in isoamyl alcohol enable fabricating a lossless charge recombination layer for efficient inverted tandem and triple‐junction solar cells for a range of polymer‐fullerene photoactive layers without adjusting the deposition conditions.